PRECLINICAL TOXICITY STUDIES OF AERIAL PARTS OF WALSURA PISCIDIA ROXB: Pharmaceutical Science-Pharmacognocy - I. SARATH CHANDIRAN; K. B. CHANDRA SEKHAR; DEEPAK KUMAR (International Journal of Life Science and Pharma Research, 2022)
The present study was aimed to evaluate the safety of aqueous and ethanolic extracts of aerial part of Walsura piscidia Roxb. (AEWP & EEWP) by determining their potential toxicity after acute and 28-day repeated dose administration in Wistar Albino rats. Acute and 28-day repeated dose oral toxicity studies were performed by following OECD test guide lines 423 and 407 respectively. In acute toxicity study no treatment related death or toxic signs were observed with AEWP and EEWP administration. In repeated dose study no significant differences in bodyweight changes and hematology was observed between control and AEWP and EEWP groups. Conversely there was a decrease in serum glucose and cholesterol levels and increase in protein levels in treated rats compared to control. No gross pathological findings and difference in relative organ weights were observed between control and test drug treated rats. Histopathological examination revealed no abnormalities with the test drug treatment. Acute toxicity study reveals that LD50 of AEWP and EEWP is greater than 2000mg/kg bwt in fasted female rats and can be classified under category 5. The 28 days. repeated oral toxicity study justified that the No Observed Adverse Effect Level (NOAEL) of Walsura piscidia Roxb is greater than 800mg/kg bwt/day p.o in rats. There were no delayed effects in satellite group. In conclusion GS was found to be non toxic in tested doses and experimental conditions.